Visualization of Perineuronal Nets in Central Nervous System Tissue Sections - Souter, Luke; Kwok, Jessica C F (Methods in molecular biology, 2020)
The perineuronal net (PNN) is a specialized extracellular matrix structure that surrounds subpopulations of neurons in the central nervous system (CNS). The appearance of PNNs on the cell surface marks the closure of the critical period during development and has been observed to reduce synaptic plasticity. Perineuronal nets comprise hyaluronan, chondroitin sulfate proteoglycans (CSPGs), link proteins, tenascin-R, and other components, some of which are substrates for a disintegrin-like and metalloprotease domain with thrombospondin type 1 motifs (ADAMTS) proteases. There is a high heterogeneity of PNNs in the CNS. Depending on which part of the CNS is studied, the PNNs may be observed surrounding the soma, or both the soma and proximal dendrites. The most robust marker for PNN is a lectin called Wisteria floribunda agglutinin. Here, we describe a method for preparing tissue for visualization of PNNs in CNS.
Keywords: receptory N-acetylglukosaminu; centrální nervový systém; Plant Lectins; Microscopy, Confocal; Receptors, N-Acetylglucosamine; rostlinné lektiny; Animals; Central Nervous System; imunohistochemie; Immunohistochemistry; zvířata; konfokální mikroskopie; Extracellular Matrix; extracelulární matrix